Insights Into Clozapine’s Kinetic Interactions: Enzymatic Inhibition of CYP1A2 by Ciprofloxacin and Norfloxacin - CHIRALI, Ana-Elena; CIOCOTIȘAN, Iulia Maria; VLASE, Ana-Maria; MUNTEAN, Dana Maria; VLASE, Laurian (Studia Universitatis Babeș-Bolyai Chemia, 2024)
This study aimed to evaluate the kinetic interactions between clozapine (CLZ) and the fluoroquinolone antibiotics ciprofloxacin and norfloxacin using a systematic three-step compartmental modelling approach. Clozapine, primarily metabolized by CYP1A2 and CYP3A4, is known to exhibit altered kinetics when co-administered with fluoroquinolones due to their inhibitory effect on CYP1A2. The proposed models evaluated the absorption, distribution, metabolism, and elimination (ADME) of clozapine and its active metabolite, N-desmethyl clozapine (CLZ-M), under both reference conditions and in the presence of these antibiotics. The selected kinetic models demonstrated a strong correlation between experimental data and predictions (R² > 0.96), providing robust insights into the mechanisms underlying these interactions. Ciprofloxacin and norfloxacin significantly affected CLZ's presystemic and systemic metabolism, with ciprofloxacin altering relative bioavailability more prominently. These findings emphasize the necessity of dose adjustments for clozapine in clinical practice to mitigate potential adverse effects due to higher drug exposure when co-administered with fluoroquinolones. This study offers a mechanistic framework for understanding complex drug-drug interactions and optimizing dosing strategies in combined therapeutic regimens.